2017
DOI: 10.21873/invivo.11031
|View full text |Cite
|
Sign up to set email alerts
|

PET Probe-Guided Surgery in Patients with Breast Cancer: Proposal for a Methodological Approach

Abstract: Nuclear medicine has an essential and increasing role in the management of patients with breast cancer. Sentinel node detection has achieved reliability and, at present, it has an important place in clinical management. Even in the era of gene-expression profiling, nodal status remains one of the primary prognostic discriminants in patients with breast cancer, and is of great value as an independent predictor of distant disease development. Although several institutional case series have differed in patient se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…Therefore, histological examination of the biopsies' sample at the end of NAC is essential before subsequent surgical treatment. In our opinion, either molecular or nuclear dedicated breast imaging could improve the sensibility and complete surgical resection of any residual tumors (39)(40)(41). Additionally, EFS and OS indices have been calculated and proven to be greater, as also reported in literature, in those patients who obtained pCR.…”
Section: Discussionmentioning
confidence: 64%
“…Therefore, histological examination of the biopsies' sample at the end of NAC is essential before subsequent surgical treatment. In our opinion, either molecular or nuclear dedicated breast imaging could improve the sensibility and complete surgical resection of any residual tumors (39)(40)(41). Additionally, EFS and OS indices have been calculated and proven to be greater, as also reported in literature, in those patients who obtained pCR.…”
Section: Discussionmentioning
confidence: 64%
“…Application of the same protocols in breast surgery might allow length of stay and opioid use to be reduced, with an even faster prompt resumption of common activities of daily life and freeing-up of hospital beds (32)(33). The breast cancer surgery ACOSOG Z0011 (Alliance) randomized clinical trial demonstrated the non inferiority of SLNB alone compared to axillary node dissection in patients with SLNB metastases treated with BCS, increasing the number of procedures that can be completed under local anesthesia alone (37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear imaging modalities, single photon emission computed tomography (SPECT) and positron emission tomography [64], are non-invasive whole-body imaging technologies, valued for their sensitivity and limitless depth of penetration. 2D scintigraphy and 3D SPECT employ nuclides like Technetium-99m ( 99m Tc, t1/2 6 h) and Indium-111 ( 111 In, t1/2 2.8 days), that emit gamma photons of varying energies, which are then detected by gamma cameras.…”
Section: Nuclear Imaging Modalitiesmentioning
confidence: 99%
“…Though RGS using PET tracers is not as well established, it has been evaluated in the clinic to guide resection, assess lymph node metastasis in a range of malignancies, and locoregional nodal status for initial staging of breast cancer [64,70]. Most of these studies have used 18 F-FDG, typically administered a few hours prior to surgery.…”
Section: Nuclear Imaging Modalitiesmentioning
confidence: 99%
See 1 more Smart Citation